230k views
0 votes
Simplify the given expression

expression:1

9(2+ 7f)


expression:2

6•7-3^2•9+4^3


show your work

User JuZer
by
6.3k points

1 Answer

2 votes

Answer:

Expression: 1 ⇒ 18 + 63 f

Expression: 2 ⇒ 25

Explanation:

* Lets revise at first the order of operations

- The order of these operations is:

# Parenthesis

# Exponents

# Multiplication and Division which comes first from left to right

# Addition and Subtraction which comes first from left to right

- There is a word made from the first letter of each operation

PEMDAS to remember the order of operations

* Lets solve the problem

# Expression: 1

∵ 9(2 + 7 f)

- To simplify this expression multiply the bracket by 9

∵ 9(2 + 7 f) = 9 × 2 + 7 f × 9

∵ 9 × 2 = 18

∵ 7 f × 9 = 63 f

∴ 9(2 + 7 f) = 18 + 63 f

* Expression: 1 ⇒ 18 + 63 f

# Expression: 2

∵ 6 × 7 - 3² × 9 + 4³

- At first simplify exponent

∵ 3² = 9 and 4³ = 64

∴ 6 × 7 - 3² × 9 + 4³ = 6 × 7 - 9 × 9 + 64

- Solve the multiplication first

∵ 6 × 7 = 42

∵ 9 × 9 = 81

∴ 6 × 7 - 3² × 9 + 4³ = 42 - 81 + 64

- Solve 42 - 81 first because it comes first from left to right

∵ 42 - 81 = - 39

∴ 6 × 7 - 3² × 9 + 4³ = - 39 + 64

- Add them

∵ - 39 + 64 = 25

∴ 6 × 7 - 3² × 9 + 4³ = 25

* Expression: 2 ⇒ 25

User Sevin
by
5.9k points